Factors that affect the customer buying behavior towards life insurance among employees at Jabatan Ketua Menteri Melaka / Fahme Rashid and Nur Wahida Ramly - Rashid, Fahme; Ramly, Nur Wahida (Faculty of Business and Management, 2013)
Propose - The purpose of the study is to investigate the factors that affect the customer buying behavior towards life insurance among employees at Jabatan Ketua Menteri Melaka (JKMM). Design/methodology /approach – In order to gain the data, questionnaire is constructed and distributed using proportionate stratified sampling method among 553 respondents of the employees of JKMM. Reliability test are applied to examined whether the question that use are reliable or not. Multiple regressions are applied to ascertain the most factors that influence the customer buying behavior. Finding – Individual factor, insurance company, family factors, security factors and investment factors are found to have significant relationship with customer buying behavior towards life insurance. Insurance company has the highest reliability test value, thus it is the best predictor that influence the customer buying behavior towards life insurance. Practical implications – This research provide an in depth understanding on the factors that affects the customer buying behavior towards life insurance among employees at Jabatan Ketua Menteri Melaka.